PERANAN DAN TANGGUNG JAWAB MANAJER INVESTASI DALAM MENGELOLA REKSA DANA - Endang Retnowati (Perspektif, 2003)
Managing Reksa Dana investment managers have important and serious responsibility. It is related to the existence of the Reksa Dana formed, that is aimed to be an institution that collect fund from the shareholders community. The institution is one of the efforts to improve the development of Indonesia. The responsibility of investment managers include how to provide trusts to the community to invest, provide sufficient assurances for investment safety as well as profit.